Comparative study of enzymes inactivation and browning pigmentation of apple (Malus domestica) slices by selected gums during low temperature storage. Issue 6 (25th September 2018) - Sarpong, Frederick; Oteng‐Darko, Patricia; Golly, Moses Kwaku; Amenorfe, Leticia Peace; Rashid, Muhammad Tayyab; Zhou, Cunshan
Abstract: To compare and understand the ameliorative effect of coating gums and predict accurately the enzymes inactivation and browning pigmentation of apple slice in cold storage condition, this study was conducted. Three gums (Acacia senegal, Xanthan, and Karaya) coating and distilled water (used as control) were applied to apple slices and stored for 21 days. A significant ( p < 0.05) reduction in polyphenol oxidase, peroxidase, and ascorbic acid oxidase activities were achieved by these gums. The effectiveness of these gums in resisting the enzymes activities follows the order: Xanthan > Acacia > Karaya. The results show that modified second‐order polynomial model and Zero‐order kinetic model could satisfactorily describe the kinetic inactivation of enzyme activities with high R 2 (0.9524–0.99337) and browning indexes with highest R 2 values (0.94164–0.99135) and lowest values in χ 2 (0.00183–0.00346) and RMSE (0.01100–0.20536), respectively. Considering the total color change (Δ E ), Xanthan coating gums had lower Δ E value compared to others. Practical applications: The negative attributes on color, taste, flavor, and nutritional value of the fruit resulting from enzymatic and nonenzymatic browning is a major concern to the food industry. The results revealed that these gum coating could provide a promising way of preserving the integrity of apple tissues; thus, improving quality, shelf life, and marketing strategy for food processors.